Economic Environment And Political Uncertainty In Turkey, The Effect Of Political Differences Of Brand To Voters Choose - Kendirli, Hulya Cagiran (The journal of contemporary issues in business and government, 2021)
In the political uncertainty in Turkey, a long period from the date of the Republic, has been dominated by a severe economic and political uncertainty. During this period, certain political parties shaped our economic and political life. Voters, on the other hand, preferred political parties within certain frameworks. In traditional markets, just as various brands are effective in the preference of any good, in political markets, political parties are preferred with the brands they represent. In this context, the political brand for political markets consists of the party name. Symbols and logos are also used to reinforce this brand.